The environmental effects of courtyard design in Penghulu Demang Abdul Ghani Malay traditional house, Melaka / Nur Najah Mohd Sadri ... [et al.] - Mohd Sadri, Nur Najah; Misni, Alamah; Abdul Rozak, Mohd Basir; Azmi, Nurin Amalia (UiTM Press, 2024)
A courtyard in a traditional Malay house is an outdoor space surrounded by buildings or walls. The primary purpose is to provide better environmental effects for the building's indoor design. The study focuses on Melaka's traditional Malay house courtyard style, particularly in Merlimau. The study seeks to comprehend the socio-cultural values of traditional Malay house courtyard design and how the courtyard design affects the surroundings. This study examines how the courtyard establishment affects traditional Malay houses by their environmental design factors. The environmental consequences of courtyard design at Demang Abdul Ghani house, Merlimau, Melaka, were chosen for this study. The questionnaire survey was used to collect the primary data, while the data were analysed by using Statistical Package for the Social Sciences (SPSS). The primary finding revealed that the courtyard is an essential element for the environmental features used for preserving the traditional Malay environment. It also can be used to strategies the integrating between the environmental effects of the courtyards in Melaka's traditional Malay houses and the building's indoor design. The findings of traditional environmental strategies via courtyard design will contribute to the modern housing design. They will generally be the main root of mitigating the effect of climate change.